Determination of fire protection distances during a tesla model s fire in a closed parking lot - Gavryliuk, Andrii; Yakovchuk, Roman; Chalyy, Dmytro; Lemishko, Mykhailo; Tur, Nazarii (Eastern-European Journal of Enterprise Technologies, 2023)
This study modelled an electric vehicle fire on the example of a Tesla Model S (USA) in a closed car park. Such fires pose an increased danger due to their rapid spread, the presence of a large number of vehicles, the release of toxic combustion products and heavy smoke. In fact, the rapid spread of a fire in a closed car park is caused by unreasonably small distances between vehicles. Thus, the purpose of the study was to determine the minimum fire protection distances due to an electric vehicle fire in a closed car park using the example of Tesla Model 3. For this purpose, the objects and their physical characteristics were described, input and environmental parameters were set, and a mathematical model of the dynamics of fire development was formed. This made it possible to establish the minimum fire protection distance during the free development time of 610 s for an electric vehicle fire in a closed car park, which is 10 m along the flank and 6 m along the front. The difference in fire protection distances on the flank and front is explained by the design features of the electric vehicle. That is, the flank area of the flame will be larger than the front of the burning electric vehicle, and therefore the heat radiation power will also be greater. The actual heat radiation power is the key factor affecting fire protection distances. The results of the study can be used in the design of various types of car parks and the safe placement of vehicles in them. Fire protection distances between cars in enclosed car parks can be taken into account by insurance companies when assessing the risk of damage to cars due to fires. And also by fire and rescue units involved in extinguishing such fires, to ensure the safety of rescuers